MAKNA CINTA MENURUT MOHANDAS KARAMCHAND GANDHI (1869-1948): RELEVANSINYA BAGI PENGEMBANGAN SOLIDARITAS SOSIAL DI INDONESIA - , Wagiyo, Drs.,MS., Prof. Dr. H. Lasiyo, MA., MM. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The dissertation entitled The Meaning of Love According to Mohandas Karamchand Gandhi (1869-1948)